Nanoparticles for Targeted Brain Drug Delivery: What Do We Know? - Rúben G. R. Pinheiro (MDPI AG, 2021)
The blood–brain barrier (BBB) is a barrier that separates the blood from the brain tissue and possesses unique characteristics that make the delivery of drugs to the brain a great challenge. To achieve this purpose, it is necessary to design strategies to allow BBB passage, in order to reach the brain and target the desired anatomic region. The use of nanomedicine has great potential to overcome this problem, since one can modify nanoparticles with strategic molecules that can interact with the BBB and induce uptake through the brain endothelial cells and consequently reach the brain tissue. This review addresses the potential of nanomedicines to treat neurological diseases by using nanoparticles specially developed to cross the BBB.